The Effect of the 5E Learning Cycle Model Assisted by Problem-Solving-Based Student Worksheets on Student Learning Outcomes in the Material of Thermodynamics - Komalasari Komalasari; Dwi Sulistyaningsih; Eko Sujarwanto (Universitas Lambung Mangkurat, 2023)
This study examines the effect of the 5E learning cycle model assisted by problem-solving-based worksheets on student learning outcomes in thermodynamics material. The focus of the results studied includes aspects of knowledge, skills, and attitudes, especially cooperation, responsiveness, and self-confidence. This study used an experimental method with a post-test-only design. This research involved students in class XI MIPA at a high school in Singaparna. The results of hypothesis testing with the t-test and the Mann-Whitney test on student learning outcomes show that it is rejected, with a large effect size criterion. These results indicate that the 5E learning cycle model supported by problem-solving-based worksheets affects student learning outcomes in thermodynamics material. Thus, it can be concluded that the 5E learning cycle model assisted by problem-solving-based worksheets affects student learning outcomes on thermodynamics material.